(1) 2x - 3y = 2

(2) x + 2y = -20

to solve this by substitution, we choose one of the equations. from there, we choose a variable and represent it in terms of the other variable.

here, let's choose equation (2), and make variable x in terms of y:

x + 2y = -20

x = -20 - 2y

then we substitute this to equation (1):

2x - 3y = 2

2(-20 - 2y) - 3y = 2

-40 -4y - 3y = 2

-4y - 3y = 2 + 40

-7y = 42

y = -6

now we substitute this to either equations to get x,, let's substitute this to equation (2):

x + 2y = -20

x = -2(-6) - 20

x = 12 - 20

x = -8

hope this helps~ :)